PEMANFAATAN BIJI BUNGA MATAHARI SEBAGAI BAHAN BAKU FERMENTASI TEMPE - Sri Winarti; Luqman Agung Wicaksono (AGROINTEK, 2020)
Sunflower seeds are a source of vegetable protein, in 100 g seeds contain 20.78 g protein, total lipid 51.46 g, ash content 3.02 g, carbohydrate 20.0 g and 8.6 g fiber with a total energy of 2445kj. Sunflower seeds are also a source of choline (55.1 mg) and ethanolamine (35.4 mg). Judging from the nutritional value, sunflower seeds are very potential to be developed into various processed products, including tempeh. Utilization of sunflower seeds for making tempeh can produce a new food product that is rich in protein other than soybeans so that it can reduce dependence on soybean commodities. Sunflower seeds are also rich in Vitamin E which functions as a natural antioxidant for the body. The purpose of this study was to determine the effect of differences in packaging material and fermentation time on the characteristics of the tempe produced. This study used a two-factor Complete Randomized Design, namely the type of wrapper (banana leaf, teak leaf, plastic with a hole spacing of 2cm, plastic with a hole spacing of 1cm) and a factor of 2 fermentation periods (36 and 48 hours). The data obtained were analyzed using Variance Analysis (ANOVA). If there were significant differences between treatments, further tests were carried out with DMRT (Duncan) with a level of 5%. The results showed that the best treatment was the type of teak leaf wrapping and 36 hours fermentation time, which produced tempeh with the highest consumer preference value, namely texture 3.24; taste of 4.0; 3.56 color and 3.44 aroma. Characteristics of tempeh in the treatment were a total mold of 8.66 log fcu / g; total microbes 9.41 log cfu / g; vitamin E levels 24.25 mg / 100g; dissolved protein 11.93%.